Modified screening method of middle american dry bean genotypes reveals new genomic regions on Pv10 associated with anthracnose resistance - Simons, Kristin J.; Schröder, Stephan; Oladzad, Atena; McClean, Phillip E.; Conner, Robert L.; Penner, Waldo C.; Stoesz, Dennis B.; Osorno, Juan M. (Frontiers in Plant Science, 2022)
Anthracnose, caused by the fungal pathogen Colletotrichum lindemuthianum, is one of the most devastating diseases in dry bean (Phaseolus vulgaris L.) with seed yield losses up to 100%. Most anthracnose resistance genes thus far identified behave in a dominant manner and were identified by seedling screening. The Middle American Diversity Panel (MDP; n=266) was screened with a modified greenhouse screening method to evaluate the response to anthracnose race 73. Thirty MDP genotypes exhibited resistance to the race of which 16 genotypes were not known to contain anthracnose resistance genes to race 73. GWAS with ~93,000 SNP markers identified four genomic regions, two each on Pv01 and Pv10, associated race 73 resistance. A likelihood-ratio-based R2 analysis indicated the peak four SNP markers are responsible for 26% of the observed phenotypic variation, where one SNP, S10_072250, explains 23% of the total variation. SNP S10_072250 is associated with a new region of anthracnose resistance and is in an intron of a ZPR1-like gene. Further greenhouse testing of the 16 resistant lines without previously known resistance to race 73 revealed various levels of resistance under various levels of disease pressure. Disease resistance was further characterized in the field using four representative genotypes. GTS-900 and Remington exhibited field resistance while Merlot and Maverick were susceptible. Field testing with two different fungicide regimes revealed the resistant genotypes had no significant disease differences. The results suggest resistance to anthracnose may differ at various growth stages and that breeders have been selecting for major genes at early seedling stages while ignoring the effect of alternative genes that may be active at later stages. The newly identified resistant lines may be related to Age Related Resistance and could be exploited as parental sources of anthracnose resistance in addition to already known major genes. Physical localization of the multiple regions of resistance confirms the presence of two clusters of disease resistance genes on Pv01 and identifies two new regions of anthracnose resistance on Pv10 possibly associated with ARR. Future research should look at the mode of inheritance of this resistance and its effect when combined with other anthracnose resistance loci.